The Mechanics of a successful Exchange-Rate Peg: Lessons from Emerging Markets - Michael Dueker; Andreas Fischer (Swiss National Bank, Study Center Gerzensee, 2001)
To the surprise of many market watchers, Thailand's exchange-rate peg to the dollar collapsed in July 1997, leading to similar rounds of currency devaluations in other East Asian countries. This study seeks to determine if there were identifiable contrasts in implementation between Thailand's peg and a perennially successful peg. Austria's peg to the Deutsche mark.that would have hinted at problems for Thailand prior to July 1997. The comparison suggests that Thailand was not sufficiently vigilant about keeping its inflation rate low in the early 1990s. By 1995, Thailand faced a situation where a tight monetary policy involving high domestic interest rates would not always have created disinflationary pressure, as high interest rates also tended to attract greater capital inflow to Thailand. In this environment, Thailand's monetary policy became erratic and failed to maintain the exchange-rate peg.
Keywords: 330; Wechselkurspolitik; Wechselkurssystem; Inflationssteuerung; Österreich; Thailand